SHAXSLARARO MULOQOTDA EMPATIVLIKNING O’RNI - Alimirzayev Nodirbek Avazbek o’g’li (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article introduces theoretical and practical goals and provides insights about the role of empathy in interpersonal relationships and its effects on the communication process